TEACHER CREATIVITY IN THE IMPLEMENTATION OF THE 2013 CURRICULUM IN PPKN SUBJECTS AT SMPN 25 PADANG - Ornella Muty (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
This study discusses the creativity of teacher teaching in the implementation of the 2013 curriculum. The study was conducted at SMP N 25 Padang. Creativity is assessed about how teachers develop methods, strategies and also media in learning PPKn subjects. The researcher found several things related to teacher creativity in the learning process. Such as what obstacles faced by the teacher and also what efforts have been made by the school in overcoming these efforts and ways to increase the creativity and quality of teaching teachers in the classroom.The data obtained in this study come from the results of observations, interviews and questionnaire collection. Interviews were conducted with PPKn teachers, principals, and students. The questionnaire collection was carried out by researchers to get more accurate data. The data obtained by researchers is. (1) there is still a lack of creativity in PPKn teachers in the learning process. Because the teacher still cannot develop methods and learning strategies. (2) the constraints faced by teachers originate from within the teacher himself, namely the lack of the ability of teachers to use technology as demanded by the 2013 curriculum. As well as external constraints faced, namely regarding the study hours that are so dense making teachers feel difficult to prepare teaching materials. (3) the number of efforts made by the school to improve creativity and quality and help teachers to be able to adjust the way of learning with the 2013 curriculum. One of them is by involving subject teachers in training and also technical guidance on the 2013 curriculum and related subjects. The school and also the teachers always conduct evaluations and improvements to improve the quality of lessons so that the 2013 curriculum learning objectives are achieved.